A network scheme for process bus in smart substations without using external synchronization. (January 2015) - Zhao, Jiaqing; Qian, Kejun; Yao, Jianguo; Wang, Shouding; Yang, Zhihong; Gao, Zonghe; Ding, Hongen; Yang, Zhixin; Su, Dawei; Li, Huiqun; Xu, Chunlei; Huo, Xuesong; et al.
Highlights: An improved network scheme without using an external synchronization. The proposed method significantly improve the reliability of process bus network. The proposed method becomes a milestone on the road to smart grid in China. Abstract: The development of smart substations plays a crucial role in the development of smart grid. The major difference between a smart substation and an existing conventional substation lies in the process bus. Based on a thorough study over the network schemes of sampled values for process bus in smart substations, this paper summarizes and analyses major characteristics of existing network schemes. In order to overcome shortcomings of existing network schemes in time synchronization, the paper proposes a novel network scheme for process bus in smart substations without using external synchronizing clock. Compared to conventional network schemes, the proposed scheme does not need an external global synchronizing clock, thus can significantly improve the reliability of the process bus network. As a major research output of the key technological project, this work has been successfully applied to the 110 kV Shenxiang Substation in Suzhou, China.